Genetic regions affecting the replication and pathogenicity of dengue virus type 2 - Samune, Yoshihiro; Saito, Akatsuki; Sasaki, Tadahiro; Koketsu, Ritsuko; Srimark, Narinee; Phadungsombat, Juthamas; Yokoyama, Masaru; Kotani, Osamu; Sato, Hironori; Yamanaka, Atsushi; Haga, Saori; Okamoto, Toru; et al. (PLOS Neglected Tropical Diseases, 2024)
Dengue is a mosquito-borne disease that has spread to over 100 countries. Its symptoms vary from the relatively mild acute febrile illness called dengue fever to the much more severe dengue shock syndrome. Dengue is caused by dengue virus (DENV), which belongs to the Flavivirus genus of the family Flaviviridae. There are four serotypes of DENV, i.e., DENV1 to DENV4, and each serotype is divided into distinct genotypes. Thailand is an endemic area where all four serotypes of DENV co-circulate. Genome sequencing of the DENV2 that was isolated in Thailand in 2016 and 2017 revealed the emergence of the Cosmopolitan genotype and its co-circulation with the Asian-I genotype. However, it was unclear whether different genotypes have different levels of viral replication and pathogenicity. Focus-forming assay (FFA) results showed that clinical isolates of these genotypes differed in focus size and proliferative capacity. Using circular polymerase extension reaction, we generated parental and chimeric viruses with swapped genes between these two DENV2 genotypes, and compared their focus sizes and infectivity titers using FFA. The results showed that the focus size was larger when the structural proteins and/or non-structural NS1-NS2B proteins were derived from the Cosmopolitan virus. The infectious titers were consistent with the focus sizes. Single-round infectious particle assay results confirmed that chimeric viruses with Cosmopolitan type structural proteins, particularly prM/E, had significantly increased luciferase activity. Replicon assay results showed that Cosmopolitan NS1-NS2B proteins had increased reporter gene expression levels. Furthermore, in interferon-receptor knock-out mice, viruses with Cosmopolitan structural and NS1-NS2B proteins had higher titers in the blood, and caused critical disease courses. These results suggested that differences in the sequences within the structural and NS1-NS2B proteins may be responsible for the differences in replication, pathogenicity, and infectivity between the Asian-I and Cosmopolitan viruses.